A study by 1H NMR on the influence of some factors affecting lipid in vitro digestion. (15th November 2016) - Nieva-Echevarría, Bárbara; Goicoechea, Encarnación; Manzanos, María J.; Guillén, María D.
Highlights: The influence of several experimental factors on fish lipolysis was studied. 1 H NMR provides an holistic view of lipolysis reaction occurring during digestion. Up to 95% of fish triglycerides can be hydrolyzed by varying certain factors. Bile concentration greatly influences on in vitro lipid digestion. The information obtained is of great interest to design in vitro digestion models. Abstract: This article focuses on the impact of several experimental factors, including gastric acidification, intestinal transit time, presence of gastric lipase, sample/digestive fluids ratio, concentration and nature of the enzymes in intestinal juice, and bile concentration, on the extent of in vitro lipolysis when using a static model that simulates human digestion processes in mouth, stomach and small intestine. The study was carried out by Proton Nuclear Magnetic Resonance ( 1 H NMR). This technique provides a complete molecular picture of lipolysis, evidencing for the first time, whether preferential hydrolysis of certain glycerides over others occurs. A lipolysis degree similar to that reported in vivo was reached by varying certain variables within a physiological range; among them, bile concentration was found to be crucial. The holistic view of this 1 H NMR study provides information of paramount importance to design sound in vitro digestion models to determine the bioaccessibility and bioavailability of lipophilic compounds.